Identification of Candidate Biomarkers for Quality Assessment of Hatchery-reared Mussel Larvae Via GC/MS-based Metabolomics - Young, T; Alfaro, AC; Villas-Bôas, S (Taylor and Francis Ltd, 2015)
To ensure environmental and economic sustainability of future aquaculture growth, large-scale hatchery production of mollusc larvae is required. However, variation in larval quality currently limits potential maximum yields. Identification of biomarkers which reflect the immediate physiological condition of larvae during hatchery production could help monitor and determine causes of variation. Metabolomics is well-suited to this task due to its capacity for providing an instantaneous snapshot of the physiology of an organism through analysis of its metabolite profile. As a test, we applied GC/MS-based metabolomics for this purpose. Using a variety of univariate and multivariate feature selection methods, we identified four metabolite–metabolite ratios involving levels of succinate, glycine, alanine, pyroglutamate and myristic acid as candidate biomarkers for assessing mussel larval quality. These metabolites are known to have roles in energy metabolism, osmotic regulation, immune function and cell–cell communication. We anticipate that further investigation of these metabolites and their associated biochemical pathways will yield a more complete understanding of the factors responsible for larval production variability.
Keywords: Aquaculture; Bivalves; Larval physiology; Larval quality; Metabolite profiles; Metabolomics; Mussel larvae; Perna canaliculus